Naked-Eye Detection of Hepatitis B Surface Antigen Using Gold Nanoparticles Aggregation and Catalase-Functionalized Polystyrene Nanospheres - Yufei Liu (ACS Omega, 2021)
Developing rapid, efficient, highly sensitive, simple, stable, and low-cost virus marker detection products that are appropriate for basic facilities is of great importance in the early diagnosis and treatment of viruses. Naked-eye detection methods are especially important when medical testing facilities are limited. Polystyrene nanospheres (PSs) with catalytic and specific recognition functions were successfully developed by simultaneously modifying catalase and goat anti-hepatitis B surface antibodies on nanospheres. The modified PSs contributed significantly to the amplification of the signal. Via the specific antigen–antibody reaction, the bifunctional nanospheres could be captured on microplate and then catalyzed the decomposition of hydrogen peroxide to reduce chloroauric acid and synthesize gold nanoparticles (AuNPs). Due to the surface plasmon resonance of AuNPs, the solution color change could be observed with the naked eye and the limit of detection (LOD) was 0.1 ng/mL. Furthermore, the LOD observed with instrumentation was 0.01 ng/mL, which meant that a rapid, efficient, and highly sensitive method for the detection of hepatitis B surface antigens was successfully developed, and neither complex sample pretreatment nor expensive equipment was needed.